2008
DOI: 10.1128/jvi.02220-07
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Putative Multisubtype Hepatitis C Virus Infections In Vivo by Heteroduplex Mobility Analysis of Core/Envelope Subgenomes

Abstract: The frequency that multiple different subtypes of hepatitis C virus (HCV) simultaneously infect a given individual is controversial. To address this question, heteroduplex mobility analysis (HMA) of portions of the HCV core and envelope 1 region was optimized for sensitive and specific detection of mixtures of HCV genomes of different genotype or subtype. Using the standard HCV genotyping approach of 5'-untranslated region (UTR) analysis, 28 of 374 (7.5%) chronic hepatitis C research subjects were classified a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 51 publications
1
13
0
Order By: Relevance
“…19,20 The wide variation may be explained by the variety of approaches used. 20 Many non-sequencing methods have been applied to detect multitypic HCV infection, which differ in terms of sensitivity to detect minority genotypes and of specificity in the assignment of genotypes. 20 Sequencing a less-conserved subgenomic region, such as envelope 1 (E1) or NS5B, is considered the "gold standard" of genotyping.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…19,20 The wide variation may be explained by the variety of approaches used. 20 Many non-sequencing methods have been applied to detect multitypic HCV infection, which differ in terms of sensitivity to detect minority genotypes and of specificity in the assignment of genotypes. 20 Sequencing a less-conserved subgenomic region, such as envelope 1 (E1) or NS5B, is considered the "gold standard" of genotyping.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21] However, the frequency of multitypic HCV infection is still controversial, with Table 2 The demographic data and virological characteristics of patients detected for multitypic HCV infection with colony analysis of core-envelope 1 regions. (1) a The earliest collected serum sample from each patient was labeled (B), and the latest collected sample was labeled (E).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All patients had HCV-related end-stage liver disease at the time of liver transplantation, and all developed recurrent HCV infection as demonstrated by the persistence of post-transplant HCV viremia. HCV genotypes were assigned using the restriction fragment length polymorphism analysis (RFLP) of the 5′-UTR region (Davidson et al, 1995) and confirmed by probe hybridization of the Core/E1 region (Li et al, 2008b). Serum samples and purified peripheral blood mononuclear cells (PBMCs) were obtained immediately prior to liver transplantation and stored at −80°C.…”
Section: Methodsmentioning
confidence: 99%
“…The ability to subtype different regions of the viral genome made it possible for HMA to identify inter-subtype recombinants (Cham et al, 2000; Heyndrickx et al, 2000; Sarkar et al, 2011; Sawadogo et al, 2003). HMA-based subtyping has also been developed for other viral pathogens, including Hepatitis C (Calvo et al, 1998; Li et al, 2008; White et al, 2000), feline immunodeficiency virus (Bachmann et al, 1997), small-ruminant lentiviruses (Germain, Croise, and Valas, 2008), Influenza (Zou, 1997) and enteric adenoviruses (Soares et al, 2004). The accuracy of HMA subtyping in many of the above studies has been evaluated using DNA sequencing and compared by some to peptide-based serologic methods (Bobkova et al, 2001; Gaywee et al, 1996; Hussein et al, 2000; Wasi et al, 1995a).…”
Section: Introductionmentioning
confidence: 99%